Road salts, human safety, and the rising salinity of our fresh waters. Issue 1 (15th November 2021) - Hintz, William D; Fay, Laura; Relyea, Rick A
Abstract : In the US, 70% of the population lives in regions that experience snow and ice. Road deicing salts reduce vehicular accident rates in these regions by >78% but have led to dramatic increases in freshwater salinity. To seek environmental management and policy solutions, we ask: (1) how much salt is used and where is it applied, (2) do current agency thresholds protect freshwater biota, (3) are deicing salts affecting our water supplies, and (4) how can we curb salinization from deicing salts? Use of deicing salts has tripled over the past 45 years and blankets much of the US. There is an urgent need to reassess inadequate thresholds to protect freshwater biota and our drinking water supplies. Given the lack of ecologically friendly and cost‐effective alternatives, broad‐scale adoption of best management practices is necessary to curb the increasing salinization of freshwater ecosystems resulting from the use of deicing salts.